Role of Dermoscopy in the Assessment of Basal Cell Carcinoma - Ungureanu, Loredana; Cosgarea, Ioana; Şenilǎ, Simona; Vasilovici, Alina (Frontiers in Medicine, 2021)
Basal cell carcinoma is one of the most common cancers in white people, with a continuous increase worldwide. Dermoscopy, a non-invasive technique, allows early diagnosis based on the presence of typical vascular structures, pigmented structures, and ulceration and the absence of specific melanocytic structures. Moreover, dermoscopy is useful in basal cell carcinoma management, enabling the differentiation between different histological subtypes, between pigmented and nonpigmented variants and allowing a more accurate assessment of surgical margins. After non-ablative therapies, dermoscopy allows the accurate detection of residual disease. The purpose of this review is to highlight the dermoscopic features encountered in basal cell carcinoma and to outline the role of dermoscopy for diagnosis and therapeutic response in this cancer.